Learning transformation rules for semantic query optimization: a data-driven approach - Shekar, S.; Hamidzadeh, B.; Kohli, A.; Coyle, M. (IEEE transactions on knowledge and data engineering, 1993)
An approach to learning query-transformation rules based on analyzing the existing data in the database is proposed. A framework and a closure algorithm for learning rules from a given data distribution are described. The correctness, completeness, and complexity of the proposed algorithm are characterized and a detailed example is provided to illustrate the framework.< >